Aerodynamic performance of a circulating airfoil section for Magnus systems via numerical simulation and flow visualization. (1st June 2016) - Kazemi, Seyed Ali; Nili-Ahmadabadi, Mahdi; Sedaghat, Ahmad; Saghafian, Mohsen
Abstract: The lift to drag ratio is the most determining factor in power efficiency of wind conversion systems such as wind turbines. The lift to drag ratio can be enhanced considerably using circulating airfoil shapes. In this research, the NACA0021 airfoil is modified and manufactured to form a treadmill like circulating shape. Aerodynamic performance of the treadmill shape is computationally and experimentally investigated. In the experiment, the smoke flow visualization is conducted in a small wind tunnel to study flow features such as separation and stagnation points. Computational method is based on the finite volume discretization of RANS (Reynolds Averaged Navier–Stokes) equations and the shear stress transport (k–ω SST (shear-stress transport)) turbulence modeling. Magnus effects are investigated under various speed ratios (speed of circulating surface to the wind speed) and several angles of attack. The numerical and flow visualization results reveal some main changes to flow features including full removal of separation zone above moving surfaces. At the speed ratio of 3, zero angle of attack and flow Reynolds number of 94, 000, an impressive lift to drag ratio of 130 is obtained for the circulating airfoil whilst the maximum attainable value is merely 45 for the original NACA0021 airfoil. Highlights: Lift to drag ratio can be enhanced considerably using circulating airfoil shapes. NACA0021 airfoil is modified to form a treadmill like circulating shape. The smoke flow visualization is conducted in a small wind tunnel. CFD simulation is conducted using RANS equations and k–ω SST turbulence modeling. Both methods reveal substantial improvement in aerodynamics performance.